1981
DOI: 10.1073/pnas.78.11.7143
|View full text |Cite
|
Sign up to set email alerts
|

Na and K dependence of the Na/K pump in cystic fibrosis fibroblasts.

Abstract: The Na and K dependence of the Na/K pump was measured in skin fibroblasts from patients with cystic fibrosis and age/sex-matched controls. Under basal conditions, there was no difference between control and cystic fibrosis cells in protein per cell, intracellular Na and K content, or Na/K pump activity (measured as ouabain-sensitive 86Rb uptake). There was no difference in the Na dependence of the Na/K pump between cystic fibrosis cells and control cells. In cells from patients with cystic fibrosis, the Na/K p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

1983
1983
1989
1989

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…More recently, however, Reznik et al (12) reported a reduced affinity of the NaK pump for external K(Rb): K,,, was 2.2 mM for normal RBC and 4.6 in CF RBC. This finding paralleled their previous report that the affinity for external K of the NaK pump in cultured CF fibroblasts was reduced compared to normal cells (13), but both of these results are inconsistent with the finding of Boucher et al (7) that CF respiratory epithelium had increased Na pump activity (7).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…More recently, however, Reznik et al (12) reported a reduced affinity of the NaK pump for external K(Rb): K,,, was 2.2 mM for normal RBC and 4.6 in CF RBC. This finding paralleled their previous report that the affinity for external K of the NaK pump in cultured CF fibroblasts was reduced compared to normal cells (13), but both of these results are inconsistent with the finding of Boucher et al (7) that CF respiratory epithelium had increased Na pump activity (7).…”
supporting
confidence: 81%
“…Accordingly, physiologically important differences in the kinetic characteristics of the transport pathways studied might have been obscured. For this reason, and in view of the more recent reports of abnormaliteis in Na pump activity in CF red cells and other tissues (7,12,13), kinetic parameters of three major cation transport pathways in red cells were measured: the NaK pump, the NaK Co system, and the ouabain and bumetanide insensitive (residual) pathway. The results indicate that all of these pathways are kinetically normal in CF red cells.…”
mentioning
confidence: 99%
“…We describe serial and cross-sectional body potassium measurements on 161 unselected CF patients between the ages of I month and 17 years to further quantify the nature of malnutrition in CF and its response to nutritional therapy. Two studies of intracellular potassium levels in CF have indicated normal intracellular concentrations of potassium in this disease (5,6).…”
mentioning
confidence: 99%